Measuring Complexity: a Confirmatory Factor Analysis Approach - Reed, John C. (Journal of contemporary criminal justice, 2017)
This study examines complexity as a measure of support for organizational redirection. This study considers whether 16 items (culture, mission, values, decentralization, policies and procedures, administrative reporting practices, weapons, contract, pay, benefits, patrol boundaries, equalization of workload, size of boundaries, communications, 10-codes, and car numbers) appropriately characterized a suppressed measure of complexity related to complex organizational change, a police department merger. The current study utilizes data collected from 390 sworn officers from two merged law enforcement agencies in Kentucky. The results of the structural equation model analysis supported the view that four factors (mission, logistics, benefits, and policy) fashion an underlying construct for measuring complexity related to organizational change/redirection. The implications of these findings are also considered.